INVESTIGATION OF PROPERTIES OF CURRENT COLLECTOR ELEMENTS AND THEIR EFFECT ON THE PERFORMANCE OF TRIBOSYSTEM «CONTACT WIRE - CURRENT COLLECTOR ELEMENT» - Bolshakov, Yu. L.; Antonov, A. V. (Science and Transport Progress, 2015)
Purpose. The paper is devoted to the detailed analysis of interrelations at the contact point of friction pair «contact wire – current collector insert». In the work it is necessary: 1) to examine quality of manufacturing of specimens of current collector elements from different manufacturers; 2) to narrow the range of hardness for carbon inserts; 3) to develop a technique of sorting carbon current collector inserts for the structural parameters. Methodology. The executed work was based on the use of the theory of reliability of technical systems and electromechanical processes. Findings. The paper studies the interrelation at the contact point of friction pair «contact wire – current col lector insert», the connection was established between the hardness and electrical resistivity. It is proposed to narrow the range of carbon inserts hardness. The method of sorting coal collector inserts in hardness was developed, and the research has revealed the discrepancy of current collector inserts with existing regulations. It was proposed to equip the pantographs slide with current collector elements using special scheme and to develop a specialized research facility, which will be possible to conduct studies of the interaction of the friction pair «contact wire – current collector insert». Originality. In the course of the study the current collector inserts the sharp structural heterogeneity and fluctuations of the density of the material along the length of the insert were established. The dependence between hardness of inserts and electrical resistivity was established. It was analyzed and concluded about the need to reduce the values of the normal range of hardness. Based on the results of the research, the experimental dependences were obtained and proposed the method for sorting carbon current collector inserts for the structural parameters. Practical value. The obtained results of coal current collector inserts define the need to use method for sorting the coal current collector inserts and the use of a special scheme for equipping pantograph slide. It will allow optimizing their work, knowing the limitations for edges in exploitation and the type of the objective function that should be achieved. The proposed measures can reduce the intensity of the electrical and mechanical wear of materials friction pair «contact wire – current collector inserts». The use of specialized research facility for the study of the friction pair, will allow carrying out the studies to determine the intensity of wear of contact surfaces of the pair of friction and the coefficient of friction at various external factors.